Global tourism and waves of terror: Perspectives from military expenditure - Simplice Asongu; Paul N. Acha-Anyi (African Governance and Development Institute (AGDI), 2019)
This study complements existing literature by investigating how military expenditure can modulate the effect of terrorism externalities on tourism. The geographical and temporal scopes are 163 countries and the period 2010-2015. The empirical evidence is based on negative binomial regressions. Terrorism externalities are measured in terms of terror-related incidents, injuries, fatalities and damaged properties. We find that military expenditure significantly lessens the destructive impact of these terror-related incidents in order to induce positive net effects on tourism. This finding is robust to all measurements of terrorism. Homicides and violent demonstrations reduce tourists' arrivals whereas the rate of incarceration of convicted offenders has the opposite effect. The analysis is extended to income levels and regions in order to provide more opportunities for policy implications. Justifications for differences in these comparative tendencies are discussed.
Keywords: D74; H56; Z32; Z38; 330; Military Expenditure; Terrorism; Tourism